Analisis Filosofis Materi Buku Ajar PAI dalam Muatan Moderasi Beragama - Juni, juni erpida; Mansur , Amril; Bakar , Abu (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
Abstract The mainstreaming of religious moderation in Indonesia, even in educational institutions by the Ministry of Religion, is a response to the increasingly extreme understanding of Islam. This extreme understanding is also found in several PAI subjects in madrasas, for this reason an analytical study of the teaching materials must be carried out. Religious moderation education also needs to be carried out by philosophically analyzing how PAI material contains religious moderation in madrasas. This research aims to explain and elaborate on the presentation of philosophical analysis in Madrasah Pai textbooks and to describe Madrasah Pai teaching materials that are not in accordance with religious moderation. This research includes library research. The research method used is content analysis with a hermeneutic-phenomenological analysis approach. The results of this research analyzed the teaching materials of Madrasah Pai books, where many inconsistencies in presentation were found, namely containing tolerance in one part and intolerance in another part as well as indications of the insertion of radicalism and extremism, there were parts in the textbook that only presented one view of religious texts, exclusively towards religious differences, gender bias and not paying attention to ethnic and cultural diversity. In the context of the philosophy of preennialism and reconstructionism, the teaching materials of pai books are more pragmatic and adapt to changing times. That is, not ideality. Todd's opinion is that religious education should aim to respect the diversity of students' religious identities which is guaranteed by the constitution. The novelty in this research is that the material influences individual understanding and attitudes towards religion and religious moderation and has implications for society regarding understanding religious moderation. Keywords: Philosophical analysis of teaching materials, Islamic Religion Education book, religious moderation Abstrak Pengarusutamaan moderasi beragama di indonesia bahkan di lembaga pendidikan oleh kementerian agama adalah merupakan respon dari semakin meningkatnya pemahaman islam yang ektrim. Pemahama ekrtim itu juga ditemukan dalam beberapa mataeri PAI di madrasah, untuk itu telaah analisis materi ajar harus dilakukan . pendidikan moderasi beragama ini juga perlu dilakukan dengan cara menganalisis secara filosofis bagaimana materi PAI dalam muatan moderasi beragama dimadrasa. Peneltian ini bertujuan untuk menjelaskan dan mengelaborasi penyajian analisis filosofis dalam buku teks pai dimadrasah dan mendeskripsikan materi ajar pai madrasah yang tidak sesuai dengan moderasi beragama. Penelitian ini termasuk penelitian library reseach. Metode penelitian yang digunakan yaitu analysis content dengan pendekatan analisis hermeneutika-fenomenologi. Hasil penelitian ini menganalisis materi ajar buku pai madrasah, dimana banyak di temukan inkonsistensi penyajian yaitu bermuatan toleransi di satu bagian dan bermuatan intoleransi di bagian lain serta terindikasi terinsersi radikalisme dan ekstrimisme terdapat bagian dalam buku teks yang hanya menyajikan satu pandangan atas teks keagamaan, eksklusif terhadap perbedaan agama, bias gender dan tidak memperhatikan keragaman etnis dan budaya.Dalam konteks filsafat prenialisme dan rekonstruksifisme materi ajar buku pai sudah lebih pragmatik dan menyesuaikan perubahan zaman. Artinya, bukan idealitas. Pendapat todd bahwa pendidikan agama seharusnya bertujuan untuk menghargai keragaman identitas keagamaan peserta didik yang dijamin konstitusi. Kebaruan dalam penelitian ini yaitu materi memengaruhi pemahaman dan sikap individu terhadap agama dan moderasi beragama serta berimplikasi kepada masyarakat tentang pemahaman moderasi beragama. Kata Kunci : Analisi filosofis Materi ajar, buku Pendidikan Agana Islam, moderasi beragama